Complete Demonstration of the Valence Electronic Structure Inside a Practical Organic Solar Cell Probed by Low Energy Photoemission. Issue 7 (4th December 2013) - Nakayama, Yasuo; Nguyen, Thanh Luan; Ozawa, Yusuke; Machida, Shin'ichi; Sato, Tomoya; Tokairin, Hiroshi; Noguchi, Yutaka; Ishii, Hisao
<x xml:space="preserve">Abstract</x> The complete electronic structure inside a practical organic photovoltaic (OPV) device consisting of a trilayer structure of copper‐phthalocyanine (CuPc), fullerene (C60), and bathocuproine (BCP) is demonstrated using low‐energy ultraviolet photoelectron spectroscopy (LE‐UPS) and photoelectron yield spectroscopy (PYS). The molecular orbital energy alignment and electrostatic potential distribution throughout the entire device is illustrated based on the LE‐UPS results. A favorable potential gradient to carry the photogenerated holes and electrons is manifested to be built spontaneously in the CuPc and BCP layers, respectively. Furthermore, the ultrahigh sensitivity measurements of LE‐UPS clearly unveil the distributions of faint density‐of‐states in the energy‐gap region in the organic films. Substantially barrierless contacts to both electrodes are fulfilled by the existence of these gap states. The electronic structure under simulated sunlight illumination is examined for the purpose of elucidating the electronic structures inside the working devices in the open‐circuit condition. These results indicate experimentally the electronic functionalities of each organic material, in particular of the BCP buffer layer, on the cell efficiency.